(untitled) (International Journal of Environmental Sciences, 2025)
Abstract This paper aims to explore the attributes of a rough finite state automaton, includ- ing separatedness, connectedness, and retrievability. It explores the interconnections between these properties, providing insights into their relationships. Additionally, this work introduces the concept of the product of two rough finite state automata, adding a novel dimension to our understanding of these computational constructs.